The BAS2IC Score: A Useful Tool to Identify Patients at High Risk of Early Progression to Severe Coronavirus Disease 2019. (1st September 2020) - Kaeuffer, Charlotte; Ruch, Yvon; Fabacher, Thibaut; Hinschberger, Olivier; Mootien, Joy; Eyriey, Magali; Greigert, Valentin; ,; Meyer, Nicolas; Fafi-Kremer, Samira; Lefebvre, Nicolas; Hansmann, Yves; et al.
Abstract: We developed a score, with easily accessible data (age, sex, body mass index, dyspnea, inflammatory parameters), to predict the risk of rapid progression to severe coronavirus disease 2019. Using a cutoff of >6 points, the negative predictive value was 87%.